2014
DOI: 10.2337/db13-1807
|View full text |Cite
|
Sign up to set email alerts
|

Prohibitin Overexpression in Adipocytes Induces Mitochondrial Biogenesis, Leads to Obesity Development, and Affects Glucose Homeostasis in a Sex-Specific Manner

Abstract: Adipocytes are the primary cells in the body that store excess energy as triglycerides. To perform this specialized function, adipocytes rely on their mitochondria; however, the role of adipocyte mitochondria in the regulation of adipose tissue homeostasis and its impact on metabolic regulation is not understood. We developed a transgenic mouse model, Mito-Ob, overexpressing prohibitin (PHB) in adipocytes. Mito-Ob mice developed obesity due to upregulation of mitochondrial biogenesis in adipocytes. Of note, Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(131 citation statements)
references
References 24 publications
7
120
0
Order By: Relevance
“…The anti-tumorigenic versus pro-tumorigenic role of PHB is likely dependent upon its sub-cellular localization, type of cancer tissue, as well as any involved signaling pathways [3,13]. Increased expression of PHB modulates signaling between mitochondria and the nucleus for mitochondrial biogenesis [14].…”
Section: Introductionmentioning
confidence: 99%
“…The anti-tumorigenic versus pro-tumorigenic role of PHB is likely dependent upon its sub-cellular localization, type of cancer tissue, as well as any involved signaling pathways [3,13]. Increased expression of PHB modulates signaling between mitochondria and the nucleus for mitochondrial biogenesis [14].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Mito-Ob and m-Mito-Ob mice share obesity and metabolic phenotype, but differ in immune phenotype and, as a result, develop two different, obesity-linked, types of tumor in a mutually exclusive manner. 46,50 Moreover, the development of adult onset type 1 diabetes or tumor in the male m-MitoOb mice in a mutually exclusive and context-dependent manner 46,71 further supports the notion that pre-existing immune status plays a crucial role in obesity-related diseases, including diabetes and different types of cancer. Furthermore, it is possible that the development of insulin resistance as a result of immune dysregulation may be one of the mechanisms for the development of type 2 diabetes and its associated cancer in lean subjects.…”
Section: Metabolic and Immune Dysregulation-common To Obesity-linked mentioning
confidence: 60%
“…The obese phenotype of transgenic mice overexpressing PHB in adipocytes (Mito-Ob) confirmed that PHB, indeed, has a role in the regulation of adipose tissue homeostasis, which appears to be primarily mediated though its mitochondrial function. 50 In addition to adipocytes, PHB may contribute to metabolic homeostasis through its role in pancreatic b-cells. This is because PHB has important role in mitochondrial function, which is crucial for b-cell function, and PHB level has been reported to be upregulated in murine and human pancreatic b-cell lines as a protective response to oxidative stress.…”
Section: Phb In Metabolic Homeostasismentioning
confidence: 99%
“…On the contrary, in a mouse model overexpressing PHB in adipocytes via aP2 promoter (Mito-Ob mouse), it was observed that PHB overexpression led to mitochondrial biogenesis upregulation but also to obesity [62]. Curiously, visceral fat augmentation was more pronounced in female Mito-Ob and brown fat was more increased in male Mito-Ob mouse [62].…”
Section: Overview Of Mitochondrial Relevance In White Adipocytesmentioning
confidence: 99%
“…On the contrary, in a mouse model overexpressing PHB in adipocytes via aP2 promoter (Mito-Ob mouse), it was observed that PHB overexpression led to mitochondrial biogenesis upregulation but also to obesity [62]. Curiously, visceral fat augmentation was more pronounced in female Mito-Ob and brown fat was more increased in male Mito-Ob mouse [62]. This obese phenotype could be explained by the fact that PHB1 may inhibit pyruvate carboxylase (PC) and, as a consequence, diminishes insulin-stimulated oxidation of glucose and fatty acid in mouse adipocytes [63].…”
Section: Journal Of Obesity and Overweightmentioning
confidence: 99%